Legal histories of empire : navigating legalities - Campbell, Lyndsay; Dorsett, Shaunnagh (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2025)
"This collection brings together an international group of scholars in order to provide new insights into the diversity of imperial legalities. Across empires, legalities were produced not just - or even - through the imperial imposition of laws and legal forms, but through local processes of negotiation and contestation. Far from the metropoles, local actors found ways to creatively navigate and subvert imperial frameworks and laws, and to create space in which to shape new legalities, responsive to local circumstance and need. Covering topics as diverse as smuggling in eighteenth century Jersey, the criminalisation of female market women in World War II-era southern Nigeria, and whiteness and race in 'sexual perversion' cases in twentieth century Malaya, the collection elaborates new legal histories of empire. Drawing from Britain, Australia, Canada, the USA, India, Sri Lanka, Africa and Malaysia, the collection brings together essays that examine the stories of the peoples of empires and shows how they constituted, experienced, navigated and subverted the legal complexities of living under empire. This book will be of interest to scholars and researchers in law and history, but also to those with relevant interests in post-colonial and cultural studies, as well as in criminology and sociology"--
Navigating legalities : legal histories of Empires / Lyndsay Campbell and Shaunnagh Dorsett -- Gerald of Wales, John Davies, and the Laws of the Irish in an English colonial perspective / Craig Lyons -- Constituting a colonial crisis : Kielley v. Carson, St. John's, 1838-43 / Lyndsay Campbell -- Recrafting subjecthood through exceptional laws in the nineteenth-century British Empire / Amanda Nettelbeck -- Making Empire : writing the 1833 Ceylon Charter of Justice and curial reform in the British Empire / Shaunnagh Dorsett -- Resisting and extending Empire : how the Acadian People shaped British and French imperial rule through the strategic use of law / Robert Hamilton -- Arbitration and Empire : the anti-adjudicatory state in Bengal and British America, 1763-1775 / Christian R. Burset.
Keywords: Law -- Great Britain -- Colonies -- History; Law reform -- Great Britain -- Colonies -- History; Great Britain -- Colonies -- Law and legislation; Law -- France -- Colonies -- History; LAW / Legal History; HISTORY / World